Pergeseran Nilai Budaya Motiayo Pada Masyarakat Petani di Desa Biluhu Tengah Kabupaten Gorontalo - Ismail, Yahya Ismail; Ibrahim, Ridwan; Tanipu, Funco; Bumulo, Sahrain (Sosiologi Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The Gorontalo ethnic community has long been familiar with the mutual cooperation system, commonly known as "Motiayo" especially in the field of agriculture. This research aims to understand how social exchanges operate within the Motiayo culture of the farming community in Biluhu Tengah Village, Gorontalo Regency. The research employs a qualitative research method with a descriptive approach. Data collection involves techniques such as observation, interviews, and documentation. The research findings indicate that social exchanges within the Motiayo culture of the farming community in Biluhu Tengah Village, Gorontalo Regency, have undergone changes. In the past, mutual assistance in agricultural activities did not involve wages or salaries. Instead, it was based on the spirit of helping one another, and landowners would provide food as a gesture of gratitude to those who helped ease the workload. Moreover, landowners would willingly assist others without expecting any payment in return. However, this practice has faded away. Today, the Motiayo culture has experienced significant transformation, with all activities in the agricultural sector now adhering to standardized wages or salaries that farmers must provide to those who assist with farming tasks, from planting to harvesting. The current wage rate is approximately Rp. 50,000 per person for half a day's work (from 6 AM to 12 PM) and Rp. 100,000 for a full day's work (from 6 AM to 5 PM).